Ukraine says it has busted Hungarian spy ring collecting military data - Walker, Shaun (The Guardian, 2025)
Two Ukrainians arrested as authorities claim operation had one eye on a possible future military incursion
Keywords: Europe; Hungary; Ukraine; Viktor Orbán; World news